MEDIATING PRECARITY THROUGH MOBILE APPS - Glover-Rijkse, Ragan; Stone, Melissa; Fletcher, Megan Alyssa; Eapen, Gayas (AoIR Selected Papers of Internet Research, 2020)
This panel analyzes the use of mobile apps to mediate experiences of precarity—that is threats to life and livelihood itself. While we acknowledge that mobile apps offer opportunities to form networks of resistance, many apps also pose substantial risks to users. To begin to articulate these risks, the presentations in this panel consider case studies of several apps targeted at mediating experiences of precarity. First, we offer an analysis of “safety-oriented mobility” apps, which help users to avoid location-specific instances of harassment and violence. This presentation argues that that these apps can reinforce harmful homogeneity in spaces, enable surveillance of marginalized populations, and provide a false sense of security to users. Following this, we examine apps that have responded to intimate partner violence. In this presentation, we suggest that these mobile apps do very little to protect their users from harm and, instead, provide a short-term distraction from underlying issues. Finally, we look to LBGTQ+ apps aimed at finding romantic partners or coordinating sexual encounters through location sharing. In this presentation, we suggest that these apps pose risks of unwanted exposure and discrimination, particularly due to an uptick in data breaches and leaks. We conclude this panel by offering a collective statement that argues for systemic intervention addressing the inequalities within society but, until that time comes, we argue for measures that secure these mobile apps (and the data contained therein) and protect their users.